Single‐Lens Light‐Sheet Fluorescence Microscopy Based on Micro‐Mirror Array. Issue 8 (20th May 2022) - Cai, Yanhui; Chen, Yizhu; Xia, Yiqiu; Zheng, Siyang; Liu, Zhiwen; Shi, Kebin
Abstract: Conventional light sheet fluorescence microscopy (LSFM) utilizes two perpendicularly arranged objective lenses for optical excitation and detection, respectively. Such a configuration often limits the use of high‐numerical‐aperture (NA) objectives or requires specially designed long‐working‐distance objectives. Here, a LSFM based on a micro‐mirror array (MMA) to enable light sheet imaging with a single objective lens is reported. The planar fluorescent emission excited by the light sheet illumination is collected by the same objective, relayed onto an MMA and detected by a side‐view camera. The proposed scheme makes LSFM compatible to single objective imaging system and shows promising candidacy for high spatiotemporal imaging. Abstract : A single‐lens light‐sheet fluorescence microscopy is reported by utilizing a high aspect ratio micro‐mirror array. The planar fluorescent image is excited and collected by a single objective simultaneously, and detected on 2D camera by using the micro‐mirror array. The proposed scheme enables the use of high numerical aperture objective lens and therefore high spatial resolution in light‐sheet microscopy.